STRES DENGAN MOTIVASI BELAJAR MAHASISWA REGULER FAKULTAS KEDOKTERAN UNLAM YANG SEDANG MENYUSUN KARYA TULIS ILMIAH (KTI) - Raudah, Farida; Budiarti, Lia Yulia; Lestari, Dhian Ririn (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2015)
In learning process, the students who were preparing scientific papers need learning motivation inorder to achieve satisfactory results even though it would be full of challenges and obstacles thatwere able to cause stress. The purpose of this study was to analyzed the relationship between stressand learning motivation of regular students of medical faculty of Lambung Mangkurat University whowere preparing scientific papers. The quantitative methods were employed in this study, and thecorrelational study with cross-sectional approach was the design of the study. The number ofrespondents was 80 persons. The samples were gathered using proportional stratified randomsampling technique while the data were collected using questionnaires. It applied the Pearsoncorrelation test. The results of the correlation test showed that p value was 0,000 indicating that therewas a strong and meaningful relationship between stress and learning motivation of regular studentsofMedical Faculty of Lambung Mangkurat University who were preparing scientific papers.